2021
DOI: 10.3390/healthcare9091241
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Study on the Factors Associated with Long-Stay Hospitalization in a Child Neuropsychiatry Unit

Abstract: The past twenty years have seen a rapid increase in acute psychiatric symptoms in children and adolescents, with a subsequent rise in the number of psychiatric hospitalizations. This paper aims to: (a) describe the epidemiology of hospitalizations and some of the clinical and sociodemographic characteristics of pediatric patients admitted to a regional referral Complex Operative Child Neuropsychiatry Hospital Unit in Northeast Italy and (b) identify potential factors correlated with the length of hospital stay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…This study indicated that a family history of mental disorders was a risk factor for prolonged LOS in manic episodes and mixed states. Similar results were observed in pediatric and adolescent psychiatric disorder inpatients (Zanato et al, 2021). The significant correlation between a family history of mental disorders and hospitalization duration demonstrates genetic susceptibility's impact.…”
Section: Discussionsupporting
confidence: 78%
“…This study indicated that a family history of mental disorders was a risk factor for prolonged LOS in manic episodes and mixed states. Similar results were observed in pediatric and adolescent psychiatric disorder inpatients (Zanato et al, 2021). The significant correlation between a family history of mental disorders and hospitalization duration demonstrates genetic susceptibility's impact.…”
Section: Discussionsupporting
confidence: 78%
“…Hospital admissions of young people with mental disorders are increasing in a number of high-income countries [15,25,26]. This increase is at least partly due to increasing awareness and diagnosis of mental disorders in young people, along with a potential increase in risk factors for young people, including poor psychological health, genetic vulnerability stemming from a family psychiatric history, and adverse environmental conditions and interactions [25]. In the US, mental disorders were the most commonly given reason for hospital admissions of young person who had existing health conditions [27].…”
Section: Discussionmentioning
confidence: 99%
“…Hospital admissions for treatment of mental disorders in young people are influenced by a number of factors, including both the availability of specialist hospital beds [25], hospital admission policies, and also the availability of community-based alternatives and care pathways [31]. In 2018-19, the majority of public hospital beds allocated for mental health admissions in Australia were for general adult services (71.4%; 5,002 beds), with only 4.3% (303 beds) allocated for child and adolescent services [45].…”
Section: Discussionmentioning
confidence: 99%
“…The multidisciplinary evaluation carried out during hospitalisation includes neuropsychiatric interviews for the patient and parents; neuropsychological assessment to evaluate the patient’s cognitive and executive functioning; administration of projective tests and structured and/or semi-structured questionnaires; and the observation of family interactions through the Lausanne Trilogue Play (LTP) procedure [ 23 – 25 ].…”
Section: Methodsmentioning
confidence: 99%